Pharmacokinetic Drug‐Drug Interaction Study of Omecamtiv Mecarbil With Omeprazole, a Proton Pump Inhibitor, in Healthy Subjects. Issue 1 (16th July 2021) - Trivedi, Ashit; Sohn, Winnie; Jafarinasabian, Pegah; Zhang, Hanze; Terminello, Bianca; Flach, Stephen; Abbasi, Siddique; Dutta, Sandeep; Lee, Edward
Abstract: Omecamtiv mecarbil (OM) is a novel cardiac myosin activator in development for the treatment of heart failure (HF) with reduced ejection fraction. OM is administered as a 25‐, 37.5‐, or 50‐mg modified‐release formulation in patients with HF. Proton pump inhibitors are one of the most commonly prescribed drugs in this patient population. Given the potential for coadministration of both drugs in patients with HF, we evaluated the potential for omeprazole to affect the pharmacokinetics of OM in an open‐label study in 14 healthy subjects. Subjects received a single 50‐mg dose of OM on day 1, followed by 40‐mg once‐daily doses of omeprazole on days 4 to 8. On day 9, a single 40‐mg dose of omeprazole was administered first and immediately followed by 50‐mg of OM. Blood samples were collected up to 144 hours after dosing following administration of OM on days 1 and 9 to characterize plasma concentrations of OM. The ratios of the geometric least‐square means (90% confidence intervals) of OM coadministered with omeprazole compared to OM alone were 94.5% (81.7%‐109.3%), 94.3% (81.5%‐109.1%), and 101.2% (95.4%‐107.3%) for area under the plasma concentration–time curve from time 0 to infinity, area under the plasma concentration–time curve from time 0 to the last measurable concentration, and maximum observed plasma concentration, respectively. Coadministration of OM with omeprazole was not associated with any clinically significant pharmacokinetic drug interactions. Single doses of OM were safe and well tolerated when coadministered with omeprazole.